Pendidikan Perilaku Religius Penghuni Rumah Susun Kota Pasuruan Dalam Menciptakan Baiti Jannati - Dewi Masitah (IAI Darussalam, 2021)
The Pasuruan city government has built flats in three sub-districts. The apartment in the city of Pasuruan is expected to be a home that protects their family with limited facilities but full of comfort with the aspiration to form a sakinah mawaddah wa rahma family as well as my home to be my paradise. Likewise with an Islamic environment, ethical and interacting with harmonious neighbors. These flats are expected to be their intermediary in achieving their welfare. Building a household in a household with the concept of my home is my heaven (baiti Jannati) in an apartment is very difficult because of the large number of residents and the concept of apartment building is so complex, except with hard effort. of the residents of the apartment. Therefore, special assistance is needed from tertiary institutions based on pesantren to create education and religious behavior for the residents of the apartment so that baiti jannati will automatically be created by itself. This mentoring uses the ABCD mentoring method involving the residents of the flats themselves. The results of our assistance in these flats include the formation of religious families, polite and able to interact with the community in safe harmony and preserving congregational prayers, Islamic studies, jamiyah tahlil, dibaan and TPQ for children.